Characteristic aspects of marketing authorisation and quality assurance of bacteriophage medicinal products in the Russian Federation - D. S. Davydov; R. L. Parfenyuk; Z. V. Durmanova; V. A. Merkulov; A. A. Movsesyants (Биопрепараты: Профилактика, диагностика, лечение)
The development and introduction of new bacteriophage-based medicinal products for human use is an important mission aimed at curbing the spread of infectious diseases caused by multi-resistant pathogens. The current global practice offers two approaches to the production of bacteriophage preparations: a systemic one, with regulatory participation of state control bodies, and a personalised one.The aim of the study was to analyse the legal and regulatory framework and differences of the mentioned methodological approaches to commercial and personalised production of bacteriophage medicinal products for human use in the Russian Federation and to identify the main stages for a comprehensive approach to the development of such medicinal products with the view of improving the state regulation and control intended to ensure the quality, efficacy, and safety.The article considers the experience of therapeutic bacteriophage use in Europe, the USA, and Russia, highlighting the main reasons for the termination of commercial bacteriophage production abroad and the success of phage therapy and prophylaxis development in the Soviet Union. Currently, the Russian Federation is the only state in the world that officially implements compendial quality standards for bacteriophage preparations. The article presents the advantages and disadvantages of the systemic and the personalised approaches to the production of bacteriophage preparations and analyses legal and regulatory documents governing it in the Russian Federation. The authors note that despite the relevance of personalised approaches to treatment and prevention of human infectious diseases, the legal grounds for the personalised use of bacteriophages are practically absent both in the Russian Federation and in other countries. To support the state control and supervision over the therapeutic and prophylactic bacteriophage preparations produced for the use in the framework of the personalised approach, the authors determined the main production and quality control stages for bacteriophage medicinal products.